2021
DOI: 10.1001/jamapediatrics.2020.4678
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Youths Treated With Psychotropic Polypharmacy in the United States, 1999 to 2015

Abstract: than deaths involving opioids alone. Of the polysubstanceinvolved opioid overdose deaths, stimulants were most commonly involved.Our results are consistent with data from the general adult population, which shows stimulant-involved opioid overdose deaths increasing over the past decade. 3 Moreover, our study is consistent with data demonstrating that cocaine is now the substance most commonly coinvolved in opioid overdose deaths. 5 Limitations of this study include potential death misclassification, inaccurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Table 1 identifies key characteristics for comparison of polypharmacy outcomes in 6 studies with increased growth starting in the early ‘90s ( 28 ). Major conclusions include: First, Zhang, dosReis et al ( 19 ) showed that across 22 years, the continued growth of regimens of 3 or more concomitant psychotropic classes through 2015 was unmistakable, affecting nearly 300,000 youth treated with complex psychotropic medication regimens ( 19 ). Treatment for ADHD, even without comorbidities, is common among complex regimens of U.S. youth ( 25 ), often with an antipsychotic and stimulant, a combination with questionable pharmacologic rationale ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 identifies key characteristics for comparison of polypharmacy outcomes in 6 studies with increased growth starting in the early ‘90s ( 28 ). Major conclusions include: First, Zhang, dosReis et al ( 19 ) showed that across 22 years, the continued growth of regimens of 3 or more concomitant psychotropic classes through 2015 was unmistakable, affecting nearly 300,000 youth treated with complex psychotropic medication regimens ( 19 ). Treatment for ADHD, even without comorbidities, is common among complex regimens of U.S. youth ( 25 ), often with an antipsychotic and stimulant, a combination with questionable pharmacologic rationale ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the trends are clear, although study designs are varied and metrics are imprecise so that their implications can be missed. Nonetheless, we appreciate that some studies demonstrate clear, complete and precise profiles of prescribing patterns (19,24,40,46). The decision to limit analysis to U.S. studies was based on the authors' knowledge of the literature broadly in the past 30 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that significant proportions of youth in the most intensive level of care receiving 2, 3, and 4 or more classes of psychotropics provides data for future studies to evaluate the benefits and risks of common combinations. We endorse the call for additional research on complex inter-class regimens that has been made repeatedly (1,4,5,7,30). Research studies on the benefits and risk of combined treatment would address the evidence gap challenging psychiatrists providing clinical care, provide data regarding the effectiveness for populations, and tackle questions regarding the safety of chronic exposure to concurrent psychotropics.…”
Section: Clinical Research and Policy Implicationsmentioning
confidence: 96%
“…retrospective cohort study using 2012-2015 claims data found 38% of youth on psychotropic medication for at least 90 days were prescribed two or more psychotropic medications during the study period (1). A cross sectional study used national household survey data, and found the number of youths younger than 18 years treated with three or more psychotropic classes increased from 101,836 (1999)(2000)(2001)(2002)(2003)(2004) to 293,492 (2011-2015) (5).…”
mentioning
confidence: 99%